Urinary Tract Infections after Kidney Transplantation in Fourteen Medical Centers in Turkey - Arslan, Hande; Demirkaya, Melike H.; Ak, Oznur; Aydin, Mehtap; Aydin, Gule; Aypak, Adalet; Bayindir, Yasar; Demiroglu, Ziya; Ergen, Pinar; Ersoz, Gulden; Gundes, Sibel; Kazak, Esra; et al. (LIPPINCOTT WILLIAMS \& WILKINS, 2018)
27th International Congress of the Transplantation-Society (TTS), Madrid, SPAIN, JUN 30-JUL 05, 2018